Community Engagement for Educational Innovation: Implementing the SOLO Taxonomy to Foster Higher-Order Learning at Yala Rajabhat University, Thailand - Wanda Nugroho Yanuarto; Gunawan; Ira Hapsari; Sainee Tamphu (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Community engagement plays an important role in promoting educational innovation and enhancing higher-order learning in higher education. This community engagement program aimed to introduce and implement the Structure of the Observed Learning Outcome (SOLO) Taxonomy to support students' higher-order thinking skills at Yala Rajabhat University, Thailand. The program was delivered through an international academic collaboration involving interactive lectures, collaborative discussions, case-based learning, and practical activities focused on designing learning tasks using the SOLO Taxonomy. Program effectiveness was evaluated using pre- and post-program assessments, participant observations, reflective feedback, and satisfaction questionnaires. The results indicated improved understanding of the SOLO Taxonomy and greater ability among participants to design and analyze learning activities that promote relational and extended abstract thinking. Participants also reported increased confidence in applying reflective and critical thinking strategies within academic contexts. Overall satisfaction with the program was very high, highlighting the relevance of the training materials, interactive learning approach, and opportunities for international academic exchange. These findings demonstrate that community engagement based on the SOLO Taxonomy provides an effective strategy for fostering higher-order learning, strengthening pedagogical competence, and supporting educational innovation in higher education through international collaboration.